Trade Union, Managerial and Employee Perceptions of Organisational Participation and Democracy at Work - Bank, John (Cranfield University, 2006)
This synoptic paper accompanies refereed articles, chapters in books and books published between 1977 and 2001 by the author on the theme of trade union, managerial, and employee perceptions of organisational participation and democracy at work and is submitted for a PhD by Publication. It shows how these eleven publications represent a "substantial, continuous and coherentb ody of work" on the theme and demonstratesh ow they, both individually and collectively, have made an original contribution to knowledge in this specific field. The author distinguishes between direct participation and indirect or representative forms of organisational participation and claims to have made a contribution to both. During the period spanned by these twelve publications, perceptions of trade unions, management and employees about organisational participation and democracy at work have undergone great changes. In the 1970s, trade union perceptions of organisational participation and democracy at work led the TUC among others to campaign for worker directors as a form of industrial democracy to influence boardroom decisions outside the scope of collective bargaining. The Labour government of the day supported the TUC initiative with the Committee of Inquiry on Industrial Democracy chaired by Lord Bullock. The author contributed to the national debate on worker directors with the publication of his book on the British Steel Worker Directors. He also researched direct forms of employee participation such as job enrichment, job enlargement, and autonomous working groups internationally, arguing for their incorporation in industry. When the Conservative Party came to power, the worker director avenue to indirect employee participation at boardroom level was effectively blocked. The author then turned his research attention to management-led forms of direct employee participation, namely Quality Circles and Total Quality Management with their forms of employee empowerment. His publications also foster participation for leavers and survivors in corporate downsizing.